The role of aquaporin-4 and transient receptor potential vaniloid isoform 4 channels in the development of cytotoxic edema and associated extracellular diffusion parameter changes - Chmelova, Martina; Sucha, Petra; Bochin, Marcel; Vorisek, Ivan; Pivonkova, Helena; Hermanova, Zuzana; Anderova, Miroslava; Vargova, Lydia (The European journal of neuroscience, 2019)
The proper function of the nervous system is dependent on the balance of ions and water between the intracellular and extracellular space (ECS). It has been suggested that the interaction of aquaporin-4 (AQP4) and the transient receptor potential vaniloid isoform 4 (TRPV4) channels play a role in water balance and cell volume regulation, and indirectly, of the ECS volume. Using the real-time iontophoretic method, we studied the changes of the ECS diffusion parameters: ECS volume fraction α (α = ECS volume fraction/total tissue volume) and tortuosity λ (λ2 = free/apparent diffusion coefficient) in mice with a genetic deficiency of AQP4 or TRPV4 channels, and in control animals. The used models of cytotoxic edema included: mild and severe hypotonic stress or oxygen-glucose deprivation (OGD) in situ and terminal ischemia/anoxia in vivo. This study shows that an AQP4 or TRPV4 deficit slows down the ECS volume shrinkage during severe ischemia in vivo. We further demonstrate that a TRPV4 deficit slows down the velocity and attenuates an extent of the ECS volume decrease during OGD treatment in situ. However, in any of the cytotoxic edema models in situ (OGD, mild or severe hypotonic stress), we did not detect any alterations in the cell swelling or volume regulation caused by AQP4 deficiency. Overall, our results indicate that the AQP4 and TRPV4 channels may play a crucial role in severe pathological states associated with their overexpression and enhanced cell swelling. However, detailed interplay between AQP4 and TRPV4 channels requires further studies and additional research.
Keywords: Hypoglycemia; TRPV Cation Channels; Brain Edema; modely nemocí na zvířatech; Electrocardiography; Potassium; Male; Mice, Knockout; Hypoxia-Ischemia, Brain; Aquaporin 4; draslík; srdeční zástava; Somatosensory Cortex; hypotonic stress; diffusivity; hypoglykemie; mužské pohlaví; mozková hypoxie a ischemie; Heart Arrest; myši knockoutované; astrocytes; Animals; extracelulární prostor; ženské pohlaví; myši transgenní; Extracellular Space; zvířata; akvaporin 4; Disease Models, Animal; myši; ischemia; edém mozku; oxygen-glucose deprivation; somatosenzorické korové centrum; Mice; kationtové kanály TRPV; Female; Mice, Transgenic; elektrokardiografie